Universe - Sparrow, Giles; Ferguson, Richard (Dorling Kindersley Limited London, 2018)
This children's book on space exploration and travel through the Universe will inspire your child and increase their knowledge about our place in the solar system and beyond. DKfindout! Universe is ideal for school projects or for children who simply love to learn about all things about space. From the birth of stars to the mysteries of black holes, the Universe has been constantly studied to understand how it works. Learn about the Sun, our solar system, icy planets and explosive stars, far-off galaxies that powerful telescopes looking deep into space have captured, observatories and astronomy, and whole new worlds discovered by space-exploring probes in this beautifully illustrated children's book that is crammed with amazing facts. Part of the award-winning DKfindout! series, this engaging book includes amazing photography and illustrations that help children understand the wonders of the Universe. Written by experts and checked by an educational consultant